Bagaimana anda menyelesaikan (1 + 2y) / (y-4) = (4y ^ 2 + 5y) / (2y ^ 2-7y-4)?

Bagaimana anda menyelesaikan (1 + 2y) / (y-4) = (4y ^ 2 + 5y) / (2y ^ 2-7y-4)?
Anonim

# (1 + 2y) / (y-4) = (4y ^ 2 + 5y) / (2y ^ 2-7y-4) #

  • Faktornya sebelah kanan:

# (4y ^ 2 + 5y) / warna (merah) (2y ^ 2-8y + y-4) #

# (4y ^ 2 + 5y) / warna (merah) (2y (y-4) +1 (y-4) #

# = (4y ^ 2 + 5y) / (1 + 2y) (y-4) #

  • Menggunakan persamaan awal:

Batalkan (y-4) = (4y ^ 2 + 5y) / (1 + 2y) warna (merah) batalkan ((y-4) #

  • Cross-multiply

#color (merah) (1 + 2y) ^ 2 = 4y ^ 2 + 5y #

Dengan pengembangan: # -> (a + b) ^ 2 = a ^ 2 + 2ab + b ^ 2 #

#color (merah) 1 + 4y + cancel (4y ^ 2) = cancel (4y ^ 2) + 5y #

JAWAPAN

# y = 1 #

Lihatlah: